Ultrastructure of bone marrow cells in patients with autoimmune pathologies - Galina Fedotovskikh; Galiya Shaimardanova; Manarbek Askarov; Sapargul Marat; Tatyana Yezhelenko (National Scientific Medical Center, 2018)
Objective: To determine the morpho-functional state of bone marrow autologous cells at the ultrastructural level. Material and Methods: For the electron microscopic examination, bone marrow cells taken from patients with autoimmune diseases were fixed in a 2.5% solution of glutaraldehyde with post fixation in a 1% solution of osmium tetroxide, was performed according to the conventional method and enclosed in epon. Ultrathin sections were prepared on a Leica ultramicrotome, contrasted with lead citrate by Reynolds, and examined in an electron microscope called Libra 120 (C. Zeiss). Results: Morpho-functional state of autologous bone marrow cells in severe chronic pathology was characterized by mitochondrial dysfunction and signs of insufficiency of microvesicular secretory function. Conclusion: Precultivation of bone marrow cells of patients with severe autoimmune diseases restored the energetic function of mitochondria, increased the secretory activity of endosomes.